2021
DOI: 10.1155/2021/3057754
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antibacterial and Antibiofilm Activity of the MreB Inhibitor A22 Hydrochloride in Combination with Conventional Antibiotics against Pseudomonas aeruginosa and Escherichia coli Clinical Isolates

Abstract: In the era of antibiotic resistance, the bacterial cytoskeletal protein MreB is presented as a potential target for the development of novel antimicrobials. Combined treatments of clinical antibiotics with anti-MreB compounds may be promising candidates in combating the resistance crisis, but also in preserving the potency of many conventional drugs. This study aimed to evaluate the synergistic antibacterial and antibiofilm activities of the MreB inhibitor A22 hydrochloride in combination with various antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…This expression variation of these two genes strongly suggested that most of the cells in sonicated suspensions of adherent biofilms were members of biofilm consortia and not planktonic ones. As explained previously [ 44 , 45 ], the regulation of OprF and mreB leads to increased formation of biofilm and pel-exopolysaccharide. The mreB is fundamentally involved in the regulation of cellular growth, morphogenesis, and cell division.…”
Section: Discussionsupporting
confidence: 52%
“…This expression variation of these two genes strongly suggested that most of the cells in sonicated suspensions of adherent biofilms were members of biofilm consortia and not planktonic ones. As explained previously [ 44 , 45 ], the regulation of OprF and mreB leads to increased formation of biofilm and pel-exopolysaccharide. The mreB is fundamentally involved in the regulation of cellular growth, morphogenesis, and cell division.…”
Section: Discussionsupporting
confidence: 52%
“… 69 77 Furthermore, synergists that specifically engage with Gram-negative targets and subsequently cause OM disruption as a secondary effect are not discussed in this Review. 78 86 …”
mentioning
confidence: 99%
“…As for Gram-positive specific antibiotics whose activity is potentiated by OM-disrupting synergists, we have chosen to focus on clinically used agents that are most commonly evaluated for synergy with OM disrupters: erythromycin, rifampicin, vancomycin, and novobiocin. , This criterion has, for example, led to the exclusion of OM-disrupting agents for which synergy was reported with macrolide antibiotics other than erythromycin. Also, while the specific media conditions used in antibacterial assays can strongly influence the outcome of synergy studies, for the sake of brevity, we do not include this level of detail here and instead provide clear referencing of the original studies wherein such information can be found. In addition, to further streamline the Review, synergists for which an OM-disrupting mechanism was not clearly demonstrated are not here discussed in detail. Furthermore, synergists that specifically engage with Gram-negative targets and subsequently cause OM disruption as a secondary effect are not discussed in this Review. …”
mentioning
confidence: 99%
“…For example, in bacteria, the MreB actin-like protein is important for virulence, motility, and cell wall stability. Small molecule inhibitors disrupting MreB cytoskeletal protein have potent antibacterial properties against major rod-shaped pathogens including P. aeruginosa, K. pneumonia, Salmonella and pathogenic E. coli 17,18,59 . In the case of eukaryotes, actin mediates tumor-relevant processes, including cell migration, invasion, metastasis, and signal transduction pathways implicated in tumorigenesis 17 .…”
Section: Discussionmentioning
confidence: 99%